Four-Layer QoS Analysis for Multimedia Traffic over Wi-Fi Network at UPNVJ Laboratory - Inez Innocentia Rahawarin; Fajar Rahayu Ikhwannul Mariati; Achmad Zuchriadi; Andhika Octa (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
One technique to evaluate and enhance the quality of telecommunications services is to monitor and measure the Quality of Service (QoS) and the user’s Quality of Experience (QoE). This method is suitable to be performed in an area that provides public Wi-Fi for multi-user, such as Wi-Fi at the UPN Veteran Jakarta Electrical Engineering Laboratory. The survey results show that there are still many issues experienced by users regarding the availability, accessibility, retainability, and stability of the network and application services accessed. The multimedia application services analyzed in this study are WhatsApp Desktop Call (voice traffic), Zoom Meeting (video traffic), and the UPNVJ LeADS web (data traffic). The tools used for data collection are Wireshark, PRTG, router admin panel web, and Command Prompt. Based on the monitoring, it was found that: network quality degrades when connected to more than 5 devices at the same time, frequent downtime conditions can reach 54% in a day, and the average data packet traffic speed across one device is 4,34 Mbps. Based on the average calculation of the QoS parameters measured: the highest throughput value is obtained on the UPNVJ LeADS web which reaches 102,09 Kbps, the highest delay value is obtained in the WA Desktop Call which reaches 521,39 ms, the highest jitter value is obtained in the WA Desktop Call which reaches 1,21 ms, and the highest packet loss value is obtained in Zoom Meeting which reaches 2,16%. The most common issue experienced by users is the “no internet” condition on the Wi-Fi network. The solution for network optimization in this condition can be done by administration setting and network management.